Frobenius' archaeological photography at Great Zimbabwe: activating the archive as a creative space of engagement - Massie, Gordon (My University, 2017)
Images of the past survive longer than the theories they were designed originally to support; they linger on in museum displays, as illustrations in archaeologically orientated books, and as part of popular culture (Smiles & Moser 2005: 6). At a time when western audiences grew excited by the news of discoveries and became vicarious armchair explorers, photographers selected subject matter, composed and constructed photographs to meet the audience appetite, document archaeological sites and satisfy their sponsors. When German explorer Leo Frobenius led his 9th expedition 1 to South Africa, Lesotho, Zimbabwe, Namibia, Zambia, Mozambique and India from 1928 to 1930, there were photographers in the team (Wintjes 2013: 171,172). On their two visits to Great Zimbabwe, the primary objective of the team’s archaeological photographs may have been to document the monumental stonewalled site, collect archaeological data and illustrate Frobenius’ publications; however, once I started to explore the layers within these photographs as more than just re-presentations of the surface subject matter, the narratives became increasingly interesting and complex. The Frobenius photographs have an immediate striking presence as visual re-presentations of the Great Zimbabwe monumental site. I will demonstrate that, through re-looking, re-seeing and re-making, their content extends beyond continued representation of western epistemological ideology to provide a valuable source of new understandings of Great Zimbabwe at the time the photographs were taken and today. Frobenius may not have planned the layers that I examine but that is not relevant. What matters is that these photographs, much like Smiles & Moser’s anticipation, were produced for an initial purpose but almost ninety years later provide new information (Smiles & Moser 2005:6). [Abbreviated introduction; No abstract]
A Research Report submitted to the Department of History of Art, Wits School of the Arts, Faculty of Humanities, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Arts (History of Art) (by course work and research report) June 2017
Keywords: Photography in archaeology--Zimbabwe; Archaeology--Zimbabwe